Musculoskeletal function following bariatric surgery. (13th May 2013) - Iossi, Michael F.; Konstantakos, Emmanuel K.; Teel, Donovan D.; Sherwood, Richard J.; Laughlin, Richard T.; Coffey, Michael J.; Duren, Dana L.
<x xml:space="preserve">Abstract</x> Objective Bariatric surgery is an effective method for acute weight loss. While the impact of bariatric surgery on general medical conditions (e.g., type 2 diabetes) is well documented, few studies focus on physical functional outcomes following weight‐loss induced by bariatric surgery. Design and Methods We report on 50 women aged 20‐74 scheduled for Roux‐en‐Y gastric bypass (RYGB) procedure who were enrolled for a prospective 1‐year study. Height, weight, and waist circumference were recorded preoperatively and at 6 and 12 months, postoperatively. To track musculoskeletal/physical function changes, the timed‐get‐up‐and‐go (TGUG) and short‐form health survey‐36 (SF‐36) and short musculoskeletal function assessment (SFMA) questionnaires were administered. Results Patients had significant weight loss and functional improvement. At 1 year mean weight loss was 48.5 kg and mean TGUG improvement was 3.1 s. SMFA and SF‐36 also showed improvement in functional components with weight loss at 6 months and 1‐year post surgery. Significant associations were observed between TGUG and SMFA measures at all time points. Final weight at 1 year post bariatric surgery was also significantly correlated with most functional outcomes and changes in these outcomes. Partial correlations controlling for age revealed additional associations between body weight and functional outcomes, especially at the 6‐month visit. Conclusion Our results suggest that significant rapid weight loss, such as that attained by bariatric surgery, acutely improves musculoskeletal function in morbidly obese patients. Additionally, for patients with musculoskeletal disease or injury, weight loss resulting from bariatric surgery may serve as an adjunct for improving global functional outcome, and enhancing the rehabilitation potential.